COVID-19 and Anticoagulant Use: Did the Pandemic Push DOACs Ahead of Warfarin? - Fan, Bingwen Eugene; Tan, Jia Hui Melissa; Tan, Doreen Su-Yin (Seminars in Thrombosis and Hemostasis, 2025)
The coronavirus disease 2019 (COVID-19) pandemic introduced unprecedented disruptions to health care delivery, compelling rapid adaptations in anticoagulation management. Direct oral anticoagulants (DOACs), already displacing warfarin due to their convenience and reduced monitoring requirements, appeared well-positioned for broader adoption during pandemic-induced lockdowns. This commentary examines whether the pandemic catalyzed a meaningful shift in anticoagulant prescribing patterns from vitamin K antagonists (VKAs) to DOACs, drawing on data from the United Kingdom, Australia, the United States, Europe, and Asia. In the United Kingdom, national guidance led to an abrupt and large-scale switch to DOACs, with sustained changes postpandemic. In contrast, Australia and the United States exhibited continuity in preexisting trends, with modest, transient shifts that did not persist. Asian and European data revealed a gradual trajectory toward DOACs, likely driven by long-term policy and infrastructure rather than acute pandemic pressures. While no universal transformation occurred, the pandemic accentuated existing preferences and exposed system-level vulnerabilities in warfarin monitoring. The global experience suggests that the COVID-19 crisis served as a selective accelerant of DOACs adoption, where health care systems and policies facilitated change. As health systems prepare for future disruptions, equitable access to DOACs and investment in remote care infrastructure will be essential to ensuring continuity and safety in anticoagulation therapy.
Keywords: DOACs; warfarin; anticoagulation; COVID-19; telemedicine; atrial fibrillation; deep vein thrombosis